Microdroplet pull-out testing: Significance of fiber fracture results - Donghyen Lee; Jong-Hyun Kim; Seung Jun Lee; Mantae Kim; Dong-Jun Kwon (Polymer Testing)
Fiber reinforced composites are used in structural materials that required light weight and stiffness. The properties of the fibers or matrix are important, but the interfacial properties have a significant impact on the properties of fiber reinforced composite. In this study, the interfacial shear strength (IFSS) was measured using acrylic resin and epoxy resin as base materials. The chemical composition of acrylic and epoxy matrix materials was analyzed to predict the effects on IFSS. Additionally, IFSS was measured through a microdroplet pull-out test. The reliability of the experimental results was enhanced by applying a statistical analysis to IFSS results. In the case of epoxy, GF/epoxy exhibited higher IFSS to twice and half times than CF/epoxy specimens. It means that the surface treatment of the fibers has a significant impact on the interface. In the case of acrylic, IFSS could be measured for GF. But in the case of CF, IFSS was too low to get accurate results of IFSS. Through this research, methods to improve the accuracy of composite interfacial strength measurement experiments were examined, and the study suggested the need for standardized criteria to evaluate composite interfacial adhesion.